Precisely controlled preparation of an advanced Na3V2(PO4)2O2F cathode material for sodium ion batteries: the optimization of electrochemical properties and electrode kinetics. Issue 4 (7th March 2019) - Gu, Zhen-Yi; Guo, Jin-Zhi; Yang, Yang; Yu, Hai-Yue; Xi, Xiao-Tong; Zhao, Xin-Xin; Guan, Hong-Yu; He, Xiaoyan; Wu, Xing-Long
Abstract : Electrochemical properties of the Na3 V2 (PO4 )2 O2 F cathode for sodium-ion batteries are optimized by precisely controlling the preparation parameters. Abstract : Owing to the high working voltage and energy-storage density and excellent cycling stability, Na3 V2 (PO4 )2 O2 F (NVPOF) has been recognized as a promising cathode material for sodium ion batteries (SIBs). Usually, NVPOF is prepared by a high-temperature solid-state method, which easily leads to many deficiencies including large particle size, irregular morphology and poor high-rate capability. In order to avoid these deficiencies, the present study reveals a simple hydrothermal method to effectively regulate the morphology and size uniformity of the NVPOF particles and optimize the electrochemical properties by precisely adjusting the key preparation parameters including pH and temperature. It is disclosed that the optimized NVPOF prepared at pH = 7.00 ± 0.05 and 170 °C can achieve outstanding electrochemical properties in terms of high specific capacity of 123.2 mA h g −1 at 0.1 C, superior high-rate capability of 85.9 mA h g −1 at 20 C and long cycling stability ( e.g., a capacity retention up to 94.8% at 1 C after 500 cycles). All of the properties are obviously better than those of the controls obtained at other preparation parameters. The much enhanced performance should be beneficial from the short and fast Na + transport pathways because of the high uniformity and nanometer size of the NVPOF particles, making them a promising cathode material for high-performance SIBs.